2009
DOI: 10.1029/2008jd011416
|View full text |Cite
|
Sign up to set email alerts
|

Wind speed trends over the contiguous United States

Abstract: [1] A comprehensive intercomparison of historical wind speed trends over the contiguous United States is presented based on two observational data sets, four reanalysis data sets, and output from two regional climate models (RCMs). This research thus contributes to detection, quantification, and attribution of temporal trends in wind speeds within the historical/contemporary climate and provides an evaluation of the RCMs being used to develop future wind speed scenarios. Under the assumption that changes in wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
281
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 325 publications
(319 citation statements)
references
References 80 publications
28
281
1
1
Order By: Relevance
“…For example, in the analysis of daily mean wind speed data over Australia, measurements from terrestrial anemometers showed declines (a 'stilling') of −0.13 m s -1 /decade when averaged over the entire country, but two gridded wind speed datasets (including the NCEP/NCAR reanalysis output) did not exhibit temporal tendencies (McVicar et al, 2008). Further, comparisons of 10-m wind speeds from observational data sets, reanalysis products and Regional Climate Model (RCM) simulations over North America showed trends in reanalysis data sets and RCM output were generally of lesser magnitude, and frequently of opposite sign, to those manifest in observational data sets (Pryor et al, 2009). Smits et al (2005) also reported that the apparent decrease in storminess over the Netherlands based on station data was inconsistent with that based on reanalysis data, which suggested increased storminess during the same 41-years period.…”
Section: Temporal Trends In Near-surface Wind Speedsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in the analysis of daily mean wind speed data over Australia, measurements from terrestrial anemometers showed declines (a 'stilling') of −0.13 m s -1 /decade when averaged over the entire country, but two gridded wind speed datasets (including the NCEP/NCAR reanalysis output) did not exhibit temporal tendencies (McVicar et al, 2008). Further, comparisons of 10-m wind speeds from observational data sets, reanalysis products and Regional Climate Model (RCM) simulations over North America showed trends in reanalysis data sets and RCM output were generally of lesser magnitude, and frequently of opposite sign, to those manifest in observational data sets (Pryor et al, 2009). Smits et al (2005) also reported that the apparent decrease in storminess over the Netherlands based on station data was inconsistent with that based on reanalysis data, which suggested increased storminess during the same 41-years period.…”
Section: Temporal Trends In Near-surface Wind Speedsmentioning
confidence: 99%
“…For example, model simulations over Eurasia using MM5 suggested that the recent increase in surface roughness (due to landover change) explained 25-60% of the reported decline in 10-m wind speeds (Vautard et al, 2010). Since landsurface characteristics are not variable with year in the reanalysis data sets, changes in roughness length would not be characterized by the boundary data sets used within the reanalysis systems (Pryor et al, 2009). This mechanism, if confirmed, would also account for the discrepancy between temporal trends over land and water surfaces.…”
Section: Temporal Trends In Near-surface Wind Speedsmentioning
confidence: 99%
See 2 more Smart Citations
“…A decline of near-surface wind speed in recent years has been observed in China, the Czech Republic, the United States, and Australia (McVicar et al, 2008;Brázdil et al, 2009;Pryor et al, 2009;Yang et al, 2012). It has been reported that wind speed declined by 5%-15% in the midlatitudes of the NH between 1979 and 2008 (Vautard et al, 2010).…”
Section: Relationship Between Global Frictional Torque and Mean Zonalmentioning
confidence: 99%